Brasilaccoderus, a new genus of Eurypinae (Coleoptera: Mycteridae) from Brazil - Pollock, Darren A. (Zootaxa, 2006)
The Brazilian genus Brasilaccoderus is diagnosed and described as new, comprising Brasilaccoderus scaber (Champion), new combination, and B. plaumanni, new species. Important characters are illustrated, and habitus photographs and a key to species are provided. Some preliminary thoughts on a phylogenetic placement of the new genus are given.